2021
DOI: 10.4049/jimmunol.2001004
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Maturation of B7-H6 Translates into Enhanced NK Cell–Mediated Tumor Cell Lysis and Improved Proinflammatory Cytokine Release of Bispecific Immunoligands via NKp30 Engagement

Abstract: Activating NK cell receptors represent promising target structures to elicit potent antitumor immune responses. In this study, novel immunoligands were generated that bridge the activating NK cell receptor NKp30 on NK cells with epidermal growth factor receptor (EGFR) on tumor cells in a bispecific IgG-like format based on affinity-optimized versions of B7-H6 and the Fab arm derived from cetuximab. To enhance NKp30 binding, the solitary N-terminal IgV domain of B7-H6 (DB7-H6) was affinity matured by an evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 64 publications
(72 reference statements)
2
24
1
Order By: Relevance
“…Another benefit of YSD also relies in its versatility for antibody engineering. In this respect, one of the main applications of this technology is affinity maturation, which can be achieved in multiple ways (36,38,43,(48)(49)(50). This opens up the possibility to further enhance affinities of binders if needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another benefit of YSD also relies in its versatility for antibody engineering. In this respect, one of the main applications of this technology is affinity maturation, which can be achieved in multiple ways (36,38,43,(48)(49)(50). This opens up the possibility to further enhance affinities of binders if needed.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast surface display was employed to sample the resulting diversities. In this respect, yeast surface display has proven to be versatile for engineering different antibody derivatives ( 36 41 ) but also more complex molecules such as cytokines ( 42 ), ligands ( 43 ), or cysteine-rich miniproteins ( 44 , 45 ). More recently, Sahin and colleagues could demonstrate that disulfide-rich peptides can also be enriched by phage display ( 46 ), substantiating the versatility of display technologies for engineering of more complex molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The NKp30‐NKCE format with a Fc‐null moiety has been shown to induce NK cell cytotoxicity, demonstrating that NKp30 engagement is sufficient to activate NK cell functions. However, the same molecule with a human Fc‐competent IgG1 fragment resulted in more effective killing of EGFR‐overexpressing tumor cells than molecules triggering only CD16A or NKp30, demonstrating that the coengagement of several activating receptors potentiates NK cell activation [57]. Other NKp30‐NKCEs are in development.…”
Section: Nkp30‐nkcesmentioning
confidence: 99%
“…Pekar et al engineered a bispecific engager that recognizes NKp30 on the NK cells and EGFR on the tumor cells, using an antigen binding fragment (Fab) arm derived from cetuximab, and showed that NKp30 engagement was sufficient to induce NK cell cytotoxicity. However, when adding a human Fc-competent IgG1 fragment to the engager, it resulted in an almost 10-fold higher killing capacity [ 115 ]. Another example is a trifunctional NK-cell engager that targets NKp46 and CD16 on the NK cells and a tumor antigen on the tumor cell, showing better efficacy than standard monoclonal antibodies, such as cetuximab or rituximab [ 116 ].…”
Section: Future Developments In Nk Cell Therapy For Melanomamentioning
confidence: 99%